Avaliação do uso de tecnologias digitais no apoio ao processo de modelagem matemática - FURTADO, Alfredo Braga (Universidade Federal do Pará, 2017)
In this research we investigate the utilization of Digital Technologies when mathematical modeling is used as a teaching strategy in mathematics, with the purpose to evaluate the learning that occurred in this environment. To achieve this goal, we studied the Mathematical Modeling and identified a modeling perspective to be employed in work; then, we studied the use of Digital Technologies (TD) in Education, focusing on the potential and the restrictions mentioned in the literature. As theoretical basis, we studied the theories of computerization of Tikhomirov, in particular the theory of reorganization of thought and activity theory of Leontiev and Engeström and Collective Thinking of Pierre Lévy. The purpose here was to formulate a methodology for teaching Mathematics with Modeling and Digital Technologies, which took into account the necessary conditions that would ensure effective improvements in learning. Thus, we proposed a methodology that explicitly incorporates a step in the process of modeling of utilization of TD, as well as gives emphasis on formative evaluation during the teaching process, so that the developed modeling projects achieve the expected learning objectives. Conditions for success of Digital Technologies in Education were identified. The proposed methodology has been implemented for a class of discipline "Mathematical Modeling", belonging to the Undergraduate Program in Mathematics and Science Education of Institute of Math and Science Education of Federal University of Pará (PPGECM/UFPA), which allowed us to evaluate its applicability, scope, results, relevance and assumptions that need to be addressed to ensure improved learning in the context of research. The results of qualitative research are identified: respecting the constraints identified, Digital Technologies effectively empower learning. Factors that demonstrate the aforementioned learning improvement have been identified.